[PP.33.16] IN RESTRICTIVE CARDIOMYOPATHY CAUSED BY CARDIAC AL AMYLOIDOSIS A RESTRICTIVE LV FILLING PATTERN IS ONLY PRESENT IN A MINORITY OF PATIENTS. (September 2016) - Mussinelli, R.; Musca, F.; Salinaro, F.; Boldrini, M.; Raimondi, A.; Gioia, G.; Rizzola, G.; Binot, E.; Perrone, T.; Palladini, G.; Merlini, G.; Perlini, S.
Abstract : Objective: Cardiac amyloidosis is a typical form of restrictive cardiomyopathy, characterized by severe diastolic dysfunction, associated with preserved ejection fraction (EF) until the late stage of the disease in the vast majority of patients. Therefore cardiac amyloidosis patients typically fulfil the definition of heart failure with preserved ejection fraction (HFpEF). A restrictive pattern of transmitral left ventricular (LV) filling is reported as a typical hallmark of diastolic dysfunction in these patients. Design and method: To evaluate the extent of diastolic dysfunction in cardiac light-chain (AL) amyloidosis, 221 consecutive never-treated subjects were evaluated at diagnosis between 2007 and 2010, according to the International Society of Amyloidosis criteria. Further inclusion criteria were EF > 50%, and the absence of significant valve disease, previous myocardial infarction, atrial fibrillation, or chronic obstructive lung disease. The extent of diastolic dysfunction was graded according to the ESC guidelines. To this aim, transmitral Doppler early (E) and atrial (A) velocities, E deceleration time, pulmonary venous flow velocity, early diastolic tissue Doppler peak velocity (E') and E/E' ratio were recorded. Survival was assessed over a median follow-up of 35.8 months (range, 19–60 months). Results: Unexpectedly, grade III diastolic dysfunction was only present in 82/221 cardiac AL patients (37.1%), grade II and grade I diastolic dysfunction being evident in 84 (38.0%) and 55 (24.9%) patients, respectively. The extent of amyloid deposit, as assessed by interventricular septal thickness was slightly lower in grade I than in grade III diastolic dysfunction groups (14.2 ± 2.0 vs.14.7 ± 2.1 mm; p < 0.05). Both left atrial dimensions and estimated systolic pulmonary pressure progressively increased from grade I to grade III diastolic dysfunction (p < 0.01 for both). At variance with EF, the grade of diastolic dysfunction was a significant predictor of survival at a 3-year median follow-up (p < 0.001). Conclusions: A clear-cut restrictive LV filling is only present in one third of patients with overt cardiac AL amyloidosis, grade I diastolic dysfunction being present in almost one fourth of patients. Despite being an important prognostic factor, the presence of a restrictive pattern of transmitral LV filling cannot be viewed as a 'red flag' diagnostic marker in cardiac AL amyloidosis.